THE EXPERIENCE OF POSTNATAL DEPRESSION IN A SAMPLE OF ROMANIAN MOTHERS - ANDREEA BARBU; OANA BENGA (Studia Universitatis Babes-Bolyai, 2017)
ABSTRACT. Maternal postnatal depression (PND) is a prevalent condition after birth, with significant effects on both mother and child mental health. The aim of the present research was to explore the experience of postnatal depression in a sample of Romanian mothers. Within an interpretative‐ phenomenological approach, we interviewed and analyzed the data from three mothers, regarding their perception and experience of postnatal depression. All participants were screened for PND in the first place. Within the interviews, three major themes were delineated: 1) postnatal depression: experience, significance, contextualization; 2) ambivalence; 3) social support. Three specific themes also emerged: 1) worries and dysfunctional cognitions; 2) family conflict; 3) dissatisfaction with self. All three mothers recognized the concept of postnatal depression and knew its meaning. The meanings assigned by the mothers to postnatal depression, respectively to their psychological states were: disorder, tendency to harm the baby, sadness, apathy, dissatisfaction with self. Mothers' perception of their PND experience was ambivalent, changing from minimization or denial to acknowledgment. Social support was perceived as present, while emotional support was also acknowledged as understanding (of mothers' experiences). Our results depicted postnatal depression as a phenomenon experienced both in rural and urban contexts, with common and specific features among participants.